Stability of power electronic system - Miao, Linjing (Nanyang Technological University, 2020)
Power electronic system is widely used and plays a great important role in different industries, so the stability of power electronic system becomes a vital problem. To make sure that the system keeps stable, the stability criteria should be used to do the stability analysis of power electronic systems. Usually, the stability analysis of power electronic system can be divided in three parts: switch test, converter, and converters. The challenges in the three parts are as follows: In the converter part, the single converter is analyzed. The inaccurate parameters of components may affect the stability, and if the converter system is a non-minimum phase system or with the integrator in the system, the traditional stability criteria are not useful for it; For converters part, the system which is combined by several converters is discussed, such as the multiple parallel converters and grid-connected inverter with weak grid. Similar to the converter, parameters can cause instability, and the non-minimum phase system cannot use traditional stability criteria to judge the stability; In switch test part, semiconductor material, such as SiC MOSFET, the stability is sensitive to the measurement probes parasitic. The stability evaluation of the probe-device system considering the parasitic of probes is important and is also the challenge. This thesis reviews the Nyquist stability criterion for stability analysis of power electronic systems which contain non-minimum phase system and system with integrator. Stable and unstable cases of the boost converter and grid-connected inverter with weak grid are as examples for converter and converters stability analysis, respectively. Impedance models of SiC MOSFET and probes are given to analyze the impact of parasitic and do stability evaluation. All the stability analyses are verified by real-time simulation results.